A Research on Carbon Emission Reduction Mechanism Driven by Digital Economy: An Empirical Analysis of Northeast Asia with Sino-Korean Cooperative Enterprises as the Entry Point - Wu, Hao; Qu, Tianxiao (Asia Pacific Economic and Management Review, 2025)
Against the backdrop of the escalating global concern over climate change, digital transformation is emerging as a strategic tool for the industrial sector to reduce carbon emissions. This study explores the carbon emission reduction mechanisms facilitated by the digital economy, with a particular focus on Sino-Korean joint ventures operating in Northeast Asia. Based on a panel dataset of listed cooperative enterprises from China and South Korea from 2013 to 2022, we empirically examine how digital transformation (DT) affects carbon emission intensity (CEI) through green technological innovation (GTI), while considering environmental, social, and governance (ESG) practices as moderating factors. The results indicate that digital transformation significantly reduces carbon emission intensity by promoting green technological innovation, and strong ESG practices amplify this effect.